HUBUNGAN PERAN GURU DAN KEPALA MADRASAH DENGAN KUALITAS BELAJAR MENGAJAR - Ali Sukamtono; Kusnudin; Dian Triana (Arsy : Jurnal Studi Islam, 2017)
The quality of learning need to effort effectively and efficiency, so that the students also receice the quality of the knowledge and useful, also become a goverment support to develop`s mind among students.The purpose of this research is to analysis correlation teachers-role, principal-role and quality of learning at Islamic Junior School of Tribakti Pagotan Geger Madiun. The population and sample in this research is all the teachersinIslamic Yunior School of Tribakti Pagotan Geger Madiun which is 20 teachers, because the population is less than 100 in its account, then the sample is taken from that population. Design ofthis researchisquantitative research because testing relationship between three variable there is teachers-role, principal-role and quality of learning. Collecting data methods using questionnaire which is given to all the teachersinIslamic Junior School of Tribakti Pagotan Geger Madiun as the respondents than it is analyzed using pearson correlation and proceed with 17th version of SPSS software.The results of this study indicate that: (1) there is a positive significant (p = 0,002) the correlation teachers-roleand quality of learning at Islamic Junior School of Tribakti Pagotan Geger Madiun with coefficient correlation amounted 0,646(2) positive significant (p = 0,001) correlation principal-role and quality of learning at Islamic Yunior School of Tribakti Pagotan Geger Madiun with coefficient correlation amounted 0,699 (3) positive significant simultanly correlation teachers-role, principal-role and quality of learning at Islamic Yunior School of Tribakti Pagotan Geger Madiun with p = 0,002.Based on these results, the authors give advice to the chief school and all the teachers in Islamic Junior School of Tribakti Pagotan Geger Madiunto give maximize role in the class for students achievement